Dermatomyositis sine dermatitis-an unusual non classical dermatomyositis with amyopathic myopathy tale: a case report - Balaprabha, G. Ramya; Neerajakshi, P.; Kaur, Prabhdeep; Kumar, G. Nivas (International Journal Of Community Medicine And Public Health, 2025)
We report a 13-year-old girl with dermatomyositis sine dermatitis (DMSD), a rare form of juvenile DM characterized by muscle weakness without skin rash. She presented with 2 months of progressive proximal limb weakness, neck weakness, and bilateral hand paresthesias, but no skin findings. Laboratory tests showed elevated inflammation with normal creatine kinase and significant hypokalemia. Myositis autoantibody testing revealed strongly positive anti-NXP2 and anti-Ku antibodies. A diagnosis of DMSD was made. High-dose corticosteroids plus supportive care and physiotherapy led to rapid recovery. This case highlights that DM should be considered even without rash. Anti-NXP2 positivity, associated with the sine-dermatitis phenotype, aided in confirming the diagnosis. Early recognition and treatment were crucial to the good outcome.